Muscarinic receptor activity of some Malaysian plant species - Chung, L.Y.; Yap, K.F.; Mustafa, Mohd Rais; Goh, S.H.; Imiyabir, Z. (Taylor & Francis, 2005)
Muscarinic receptor binding activity was tested on 224 plant extracts obtained from more than 50 plant families found in Malaysia. The plant extracts were evaluated by a 96-well microplate filtration–based radioligand competitive assay, centered on the ability of the plant extracts to competitively displace the radioligand, [3 H]N-methylscopolamine, from binding to the muscarinic membrane receptors. The screening assay was initially carried out at 50 mg=assay point, and those showing inhibition at and above 61% were retested at 10 mg=assay point. The extracts of Ficus septica Burm. f. (Moraceae) [65.85 3.75% inhibition; mean (n ¼ 3) SD], Polyalthia microtus Miq. (Annonaceae) (32.63 1.38% inhibition), and Popowia odoardoi Diels (Annonaceae) (35.79 7.11% inhibition) at 10 mg=assay point exhibited muscarinic properties, which are worthy of further investigation.